An Analytical Study Using Biochemical Markers to Assess the Effect of Emissions on Workers’ Health in Nineveh at Badoush Cement Factory - Mohammad Khalil (Tikrit Journal of Pure Science, 2024)
This study investigated the impact of working conditions in a cement factory on the health of 64 employees. Biochemical parameters (IgE, GPT, creatinine, CBC) were compared between workers and a control group of 10 individuals not exposed to factory emissions. A significant correlation between years of employment and elevated GPT levels was revealed by the findings, suggesting potential liver stress from prolonged exposure. Smoking was associated with higher creatinine levels, IgE levels, WBC counts, platelet counts, and neutrophil counts, indicating an increased risk of kidney impairment, allergic response, and inflammation. Age-related variations were also observed, with younger workers showing higher lymphocyte counts and older workers exhibiting higher creatinine levels, particularly those with pre-existing hypertension. Our results show the obvious effect of smoking and long-term exposure on the health of cement factory workers